PENYULUHAN ANEMIA DAN KONSUMSI TABLET TAMBAH DARAH DI SMA NU MALANG - yahmiira Setyaningrum; Ein Firnanda Putri (Jurnal SADEWA, 2026)
background Iron deficiency remains a significant health problem among adolescent girls, affecting growth, cognitive performance, and overall health. Prevalence anemia in SMU NU reached 36%, which is associated with low adherence to iron tablet consumption. Purpose this community service aimed to improve knowledge about anemia and enhance adherence to iron supplementation through interactive approach using digital comic based role play. Method education role play using digital comic in 26 adolescent girls. The result showed that the proportion of participants with good knowledge increase 85% after education intervention. Regarding compliance, 85% of participants consumed iron tablet once per week, while 15% did not consumed them at all. These finding incicate that the intervention was effective in improving knowledge, however adherence to iron supplementation remain suboptimal. Therefore, continuous monitoring and evaluation are necessary to improve compliance. In conclusion interactive digital comic combined with role play is effective in enhancing  knowledge but repeated education and sustained monitoring are required to achieve long term behavioral change.